Potency of Sapu-Sapu Fish (Hypostomus plecostomus) as Feed Supplement for Local Ducks - Asnawi; Sjofjan, Osfar; Sudjarwo, Eddy; Suyadi (International Journal of Poultry Science, 2015)
The objective of this study was to evaluate the potency of sapu-sapu fish (Hypostomus plecostomus) as feed supplement for local ducks in Mataram, West Nusa Tenggara, Indonesia. The exploration method was carried out to obtain data regarding the capture up to feeding the fish to ducks. Fresh fish directly obtain from river was dried at 60°C in the oven and then analyzed for the nutrient content. The result of study showed that sapu-sapu fish contained crude protein, lipid, crude fiber and gross energy about 37.07±3.5, 16.85±4.35 and 1.92±1.09% and 4559.1±244.37 kcal/g, respectively. It contained high level of lysine and methionine but histidine and cystine were not detected. Ca and P total content were 0.4984±0.0001 and 0.1762±0.004%. Heavy metal such as Pb, Cr and Cd were detected at 4.25±0.18 ppm, 0.28±0.000 ppm and 0.87±0.03, respectively, however Hg was not detected on whole body of fish. Sapu-sapu fish contains 4.29±0.02% albumin. It is concluded that sapu-sapu fish is a potential feed supplement for ducks because it contained high levels of nutrient required by ducks.